Efeito protetor da Kisspeptina na perda óssea causada pela falta de testosterona em ratos - Thatiane Vitoi Nascimento Ramalho (2021)
Kisspeptin is an important peptide in controlling reproductive functions, being able to stimulate the gonadotropin-releasing hormone (GnRH) neurons, which in turn are directly related to the secretion of steroid hormones. Deficiency of the sex steroids, testosterone (T) and estradiol, is closely related to an increase in the rate of bone remodeling, causing marked bone loss in both men and women. However, kisspeptin also appears to exert effects on bone tissue. In this study, we evaluated the effect of kisspeptin-10 (Kp10) on bone resorption caused by lack of testosterone. Adult rats were either orchiectomized (ORX) or subjected to sham surgery (Sham). ORX rats received for 30 days daily treatments with Kp10, its antagonist kisspeptin-234 (Kp234), T, or vehicle. Metabolic parameters, plasma hormone levels, prostate and seminal vesicle weight were analyzed. Femur samples were analyzed by computed microtomography (µCT), histomorphometry, and reverse transcription followed by real-time polymerase chain reaction (qPCR). Treatment with Kp10 caused no changes in the metabolism of the animals compared to Sham or ORX group treated with vehicle. The weight of the prostate, seminal vesicle as well as the concentrations of luteinizing hormone, testosterone, estradiol and prolactin in the Kp10-treated ORX group remained similar to the vehicle-treated ORX group. In the femur, there was trabecular bone loss in the ORX rats, and Kp10 treatment prevented this effect similarly to T. Histological analyses demonstrated higher osteoblast counts and fewer osteoclasts in the ORX groups treated with Kp10 or T than in ORX rats. These effects of Kp-10 were counteracted by the antagonist Kp234. There was an increase in molecular markers of bone remodeling in the ORX group, whereas the treatemnt with Kp10 restored the expression of Rankl, Opg and Run2. However, this effect was not blocked by Kp234. These fidings demonstrate that Kp10 treatment is able to reverse bone loss caused by lack of T in the ORX rat model. This effect seems to occur independently of the hormonal actions of kisspeptin and involves modulation in the number of osteoblasts and osteoclasts.